2002
DOI: 10.1177/104538902761696689
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact Electron Gun Actuation of a Piezoelectric Polymer Thin Film Bimorph Structure

Abstract: Noncontact electron gun actuation of a bimorphmirror structure composed of two polyvinylidene fluoride layers is demonstrated. The electric field is applied to the piezoelectric structure by controlling the potential of a nickel-copper electrode on one side of the bimorph mirror and subjecting the opposite, bare side of the bimorph to an electron flux. The electrode also serves as the reflecting surface of the thin film mirror structure. Significant characteristics of this actuation approach are demonstrated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Analyzing a similar geometry, Lee et al 15 calculated influence functions for each actuator as an individual phenomena where each actuated area was mathematically treated as a separate domain with clamped boundary conditions, and fitted with an Euler-Bernoulli beam model with a correction factor. Martin et al 16,17 modelled non-tensioned mirrors as well, but introduced the significant enabling technology of a non-contact electron gun to control the voltage applied to the piezoelectric actuators.…”
Section: Review Of Modelling Effortsmentioning
confidence: 99%
“…Analyzing a similar geometry, Lee et al 15 calculated influence functions for each actuator as an individual phenomena where each actuated area was mathematically treated as a separate domain with clamped boundary conditions, and fitted with an Euler-Bernoulli beam model with a correction factor. Martin et al 16,17 modelled non-tensioned mirrors as well, but introduced the significant enabling technology of a non-contact electron gun to control the voltage applied to the piezoelectric actuators.…”
Section: Review Of Modelling Effortsmentioning
confidence: 99%
“…The voltage or electric field for controlling the shape of the thin mirror will be applied with an electron gun that deposits electrons on the mirror's electrode segments. Previous work by Henson et al (2001) and Martin et al (2001) have shown the feasibility of this electron-gun-actuation concept and the success in using it to control quasi-static tip displacement of cantilever beams. Similar experiments were performed in this work to characterize the dynamics of PVDF bimorph under electron gun excitation.…”
Section: Experimental Actuation With Electron Gunmentioning
confidence: 99%
“…Examples include plate and shell structures with patches of active materials such as shape memory alloys or piezoelectric ceramics (Wang et al, 1997;Lin and Ren, 1998;Wang and Wang, 2000;Quek et al, 2003;Aldraihem and Khdeir, 2003), piezoelectric thin film mirrors that can be actively shaped using electric fields applied by an electron flux at selected locations (Martin et al, 2000;Martin and Main, 2002), and the post-cured shape of laminated composites (Hyer, 1981). Although these applications do not lie within the scope of this work, the approach that is developed can be readily applied to these and many other related problems.…”
Section: Introductionmentioning
confidence: 99%